Performance of Intercrops in Agroforestry System : the Case of Poplar (Populus deltoides) in Uttar Pradesh (India) - Jain, Sudhir Kumar; Singh, Parmatma (Indian Forester, 1999)
Poplar, a deciduous and fast growing forest crop, is grown along with agricultural crops on fertile and irrigated land in the northern region in India. Inter-cultivation of compatible seasonal crops in the interspaces between Poplars is essential not only for generating continuous supplementary income but also for compensating the loss of agricultural commodities arising from the transfer of land to tree plantation. This study aims at evaluating the performance of intercrops with Poplar. Since yield performance of even sole crops in the study area is not good, yields of intercrops with Poplar is also low, resulting in the low incomes. Thus, farmers have not utilized the interspaces between Poplar for intercropping till the waiting period. Wheat, sugarcane and vegetables with Poplar can provide high supplementary income in the early stages and wheat can also give some income in the later stage. Right selection of intercrops and their varieties suitable to Poplar, and reduction in the trees intensity in the older age can increase the income from intercropping. Besides this, promotion of modern agricultural technology would be also helpful in improving the yield.